2011
DOI: 10.1371/journal.pone.0022408
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Dividing and Phagocytosing Retinal Microglia Express Nestin, Vimentin, and NG2 In Vivo

Abstract: BackgroundFollowing injury, microglia become activated with subsets expressing nestin as well as other neural markers. Moreover, cerebral microglia can give rise to neurons in vitro. In a previous study, we analysed the proliferation potential and nestin re-expression of retinal macroglial cells such as astrocytes and Müller cells after optic nerve (ON) lesion. However, we were unable to identify the majority of proliferative nestin+ cells. Thus, the present study evaluates expression of nestin and other neura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 93 publications
(154 reference statements)
5
42
1
Order By: Relevance
“…The morphological phase-contrast pattern observed in these cells (nuclear and cytoplasmic changes) indicates differentiation, which is supported by the specific immunofluorescent staining of specific cell lineage markers that match the different morphological changes [13,14]. A similar result was previously described by us for the differentiation of adult bone marrow-derived MSCs into neuroblasts.…”
Section: Discussionsupporting
confidence: 76%
“…The morphological phase-contrast pattern observed in these cells (nuclear and cytoplasmic changes) indicates differentiation, which is supported by the specific immunofluorescent staining of specific cell lineage markers that match the different morphological changes [13,14]. A similar result was previously described by us for the differentiation of adult bone marrow-derived MSCs into neuroblasts.…”
Section: Discussionsupporting
confidence: 76%
“…Interestingly, nestin-expressing microglia have been demonstrated to exist even in the naive brain, in variable cell numbers in the various regions analyzed (Takamori et al 2009). More recently, we have demonstrated that a subpopulation of retinal microglia expressing neural markers nestin, NG2 and vimentin also exists in the naive adult rat retina (Wohl et al 2011), displaying a similar subcellular distribution of nestin filaments as that recently reported for the brain (Takamori et al 2009). Following ON transection, the microglial fraction expressing nestin proliferates in situ and we therefore conclude that microglial nestin expression probably plays a role in the physiological self-renewal of this endogenous cell population (Wohl et al 2010;Wohl et al 2011).…”
Section: Retinal Microgliasupporting
confidence: 77%
“…More recently, we have demonstrated that a subpopulation of retinal microglia expressing neural markers nestin, NG2 and vimentin also exists in the naive adult rat retina (Wohl et al 2011), displaying a similar subcellular distribution of nestin filaments as that recently reported for the brain (Takamori et al 2009). Following ON transection, the microglial fraction expressing nestin proliferates in situ and we therefore conclude that microglial nestin expression probably plays a role in the physiological self-renewal of this endogenous cell population (Wohl et al 2010;Wohl et al 2011). Since increasing evidence suggests that CNS injury can induce neural progenitor characteristics in activated microglia of non-neurogenic regions in vivo (Wu et al 2005;Yokoyama et al 2006), we propose that this specific retinal microglial subpopulation acts as an endogenous neural progenitor-like cell after injury.…”
Section: Retinal Microgliasupporting
confidence: 77%
“…Additionally, the BM-derived microglia that repopulate the brain after irradiation and depletion also express the nestin protein. Nestin expression in microglia could be shown, for example, in early stages of optic nerve injury [70] and traumatic brain injury [71], which indicates that nestin may be required for proliferation rather than serving as a stem cell marker. Importantly, as the study by Bruttger et al (2013) used the promoter of CX 3 CR1 as a cell fate-mapping system, they show that all repopulating cells are derived from CX 3 CR1 expressing progenitor cells.…”
Section: Conditional Genetic Deletion Modelsmentioning
confidence: 99%